Pengaruh Sikap dan Sensitivitas Harga Mahasiswa Pendidikan Ekonomi Terhadap Keputusan Pembelian Produk Hijau - Ana Shofwatun Hasanah; Aniek Hindrayani; Leny Noviani (Journal on Education, 2023)
Warming of the earth's temperature and climate disruption requires humans to be aware of the environment through changes in their consumption behaviour. This study will examine attitudes and price sensitivity to purchasing decisions for labelled bottled mineral water. The study population was Economics Education students at public universities in Central Java, totalling 679, while the sample size was 252 respondents. The sample collection technique used a questionnaire which was then tested using SPSS 25. Pearson Product Moment Correlation was used for validity testing and Cronbach'sAlpha for reliability testing. Descriptive data statistics and prerequisite analysis tests were carried out before testing the hypothesis using multiple linear regression. The results showed that attitude variables (0.000) and price sensitivity (0.000) positively and significantly affected purchasing decisions for labelled bottled mineral water. The magnitude of the influence of attitude variables and price sensitivity in simulations is 58 per cent. This research is crucial because, currently, green products are very popular with the public. For this reason, it is necessary to have a study to discuss the factors that influence consumer decisions to buy environmentally friendly products.